The Role of Islamic Journalists in Coinsuring the Community towards the Provision of Hajj in 2021 in Covid-19 Pandemic Situation - M. Yoserizal Saragih (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
This paper reviews the role of Islamic journalism in convincing the public to announce the 2021 Hajj in the midst of Covid-19, which is currently confusing the public. With the aim that the public can understand what is happening in the midst of the current Covid-19 polemic. The methodology used is literature study, because the source of the research is written data that is relevant to the topic to be discussed. This paper is a descriptive analysis that aims to describe, inventory, and analyze the actual conditions regarding the role of Islamic journalism in convincing the public to report the Hajj in 2021 in a systematic, factual and accurate manner. With the results of the discussion that journalism is not only recording, conveying and disseminating information, but journalism also has an important role to the community in reporting. The role of Islamic journalism in convincing the public to report the Hajj in 2021 amid Covid-19, Islamic journalism is known as an educator (muaddib), information straightener (musaddid), reformer (mujaddid), unifier (muwahid), and warrior (mujahid). To carry out this role, Islamic journalism has the characteristic that every information in a news report must be owned by the Prophet such as shidiq (truth), amanah (trusted), tabligh (deliver), and fathonah (intelligent).